APPRAISAL ANALYSIS OF IRRIGATION SYSTEM MANAGEMENT BASED ON SUSTAINABLE DEVELOPMENT CONCEPT IN TILONG IRRIGATION AREA OF KUPANG REGENCY - Lidya Kini; Nadjadji Anwar; Theresia Sri Sidharti (Institut Teknologi Sepuluh Nopember, 2009)
The sustainable concept of irrigation system appraisal was based on Sustainable Development Concept with 3 components/pillars, Social, Economy and Environment that the balancing of that three values are that sustainable condition. According to Regulation issued by Ministry of Public Works No.30/PRT/M/2007,the irrigation system comprises of Irrigation Infrastructure, Irrigation Water, Irrigation Management Institution and Human Resources. This research combined the concepts of sustainability and irrigation system management. According to research result, there were 15 indicators of Tilong Irrigation System Sustainability based on the calculation method of AHP. The research result for Sustainable Appraisal of Tilong Irrigation System was Sub DI VII in the Sustainable condition, Sub DI V in the condition of Equitable, Sub DI II in the Sustain condition of environment, Sub DI I in the Environment Sustain Condition, Sub DI III in the Social Sustain Condition, Sub DI IV in the condition unsustain, Sub DI VI in the condition unsustain.